Singlewide Chasing the American Dream in a Rural Trailer Park - Salamon, Sonya (Cornell University Press, 2017)
In Singlewide, Sonya Salamon and Katherine MacTavish explore the role of the trailer park as a source of affordable housing. America's trailer parks, most in rural places, shelter an estimated 12 million people, and the authors show how these parks..